Case report: Thrombotic microangiopathy in pediatric multisystem inflammatory syndrome associated with COVID-19: a case series - Nalçacıoğlu, Hülya; Önal, H. Gözde; Bozkaya Yücel, Burcu; Tekcan Karali, Demet; Erdeniz, Emine; Öz Tuncer, Gökçen; Aydoğ, Özlem (Frontiers in Pediatrics, 2023)
Introduction: This report provides insight into three distinct pediatric cases exhibiting a nexus between multisystem inflammatory syndrome in children (MIS-C) and thrombotic microangiopathy (TMA) triggered by COVID-19. The aim is to underscore the range of clinical presentations and the essentiality of early interventions. Case Presentations: This report presents three cases aged ten months, seven years, and three years with persistent fever, diarrhea, nausea, and vomiting. The first case, a 10-month-old girl, demonstrated acute kidney injury (AKI) and microangiopathic hemolytic anemia (MAHA) following a COVID-19 infection. Despite initial negative SARS-CoV-2 RT-PCR results, her condition escalated rapidly, presenting increased levels of LDH (peaking at 4200 U/L) and requiring renal replacement therapy (RRT) to manage deteriorating renal function. Interventions with eculizumab and anakinra led to marked improvements, with a stable follow-up of 13 months post-hospitalization. The second case involved a 7-year-old girl who developed symptoms of MIS-C, hemolytic uremic syndrome (HUS), and posterior reversible encephalopathy syndrome (PRES) post-exposure to COVID-19, evidenced by heightened LDH levels (3522 U/L at peak). After a precarious period of deteriorating kidney function and exacerbated hypertension, she responded positively to treatments, inclusive of IVIG, steroid therapies, and eculizumab, with a favorable six-month follow-up showcasing stable laboratory results. The third case discusses a 3-year-old boy, without any medical history, manifesting HUS symptoms and COVID-19 infection. He exhibited increased LDH levels (peaking at 3946 U/L) alongside elevated creatinine, marking renal impairment. He responded well to hemodialysis, IVIG, and steroid therapy, showcasing substantial recovery by the 19th day of hospitalization, which marked his discharge with a tapering steroid regimen. Conclusions: This case series underscores that MIS-C-associated TMA is a significant complication in pediatric COVID-19. Our findings illuminate the potential for treatment success but simultaneously emphasize the need for a more comprehensive understanding of the underlying pathophysiology.